Penokohan dalam Novel Surat Cinta untuk Imamku dan Implikasinya terhadap Pembelajaran Bahasa Indonesia - Hidayat, Fahmi (Universitas Indraprasta PGRI, 2024)
This research aims to determine the characterizations contained in the novel Surat Cinta Untuk Imamku by Indriani Sonaris. The research method used to analyze this novel uses a qualitative approach with a descriptive method which aims to objectively describe the characterizations contained in the novel Surat Cinta Untuk Imamku. After the researcher analyzed, there were characterizations in the novel Surat Cinta Untuk Imamku which consisted of characterizations, namely the main character, additional characters, protogonist characters and antagonist characters. Of the 51 data found, 51% were main characters, 21.56% were antagonists, and there were at least 2 findings, namely 13.72% protogonist characters, and 13.72% additional characters. The characterizations in the novel Surat Cinta Untuk Imamku are selfish, unstable, caring, responsible, suspicious, angry, fragile.